Políticas de proteção social direcionadas às famílias de adolescentes em cumprimento de medida privativa de liberdade, no estado do Paraná, no período de 2006 a 2010 - Santos, Maria Christina dos (2013)
This paper aims to describe the policies targeted to families of adolescents in fulfillment of a custodial sentence in the State of Paraná between 2006 and 2010. It tries to answer whether the families of these adolescents were met by social protection policies in line with the provisions of the National Socio Educational System (SINASE). It begins with a description of the historical evolution of the rights of children and adolescents and follows describing the legal framework and policies directed to the family, bringing reflections on infractions and subsequently raises questions alluding to SINASE. All these reflections serve as a foundation for the research itself. The present research is pertinent to the concentration area of this Master's degree, namely, Planning and Public Policy.This is applied research, descriptive, qualitative and indirect, which uses the inductive method. Implies bibliographical and documental study which it uses as a data collection instrument and includes a non-directive interview with the manager of the Secretariat of Children and Youth of the State of Paraná between 2003 and 2010. It describes the building and evolution of the policies and physical facilities for its implementation, the transformation of the Department for Children and Adolescents (SECJ) in Secretariat for Families and Social Development (SEDS). It was concluded, despite all efforts, that the State of Paraná has not implemented policies aimed at strengthening the families of adolescents deprived of liberty.The very Secretariat for Childhood and Youth diagnosed the failure of practices involving the families of adolescents deprived of liberty, despite recognizing them as a vital link in the socioeducational process.